Jersey City, N.J., Rev. Ordinances ch. 21, §§ 1-5 (1899) - (:unkn) unknown (My University, 1873)
no person shall, within the limits of Jersey City, carry, have, or keep on his, or her person concealed, any slung-shot, sand-club, metal-knuckles, dirk or dagger not contained as a blade of a pocket knife, loaded pistol or other dangerous weapon.
Keywords: CARRY - CONCEALED